2013
DOI: 10.1051/0004-6361/201321883
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a planetary nebula surrounding the symbiotic star DT Serpentis

Abstract: We report the discovery of a planetary nebula centered on the poorly studied symbiotic binary star DT Ser. In a few other symbiotic stars spatially resolved nebulae have been discovered as well, but only one of them probably is a genuine planetary nebula, while the others are likely to originate in complex mass-ejection episodes from the interacting binary central stars that are possibly related to nova-like outbursts. The rim of the planetary nebula around DT Ser is severely distorted toward a brighter star 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Central stars of ∼20% of known PNe are reported to be close binaries (e.g., Bond 2000;Miszalski et al 2009), and it is increasing with deeper sky surveys like Kepler and Gaia (e.g., Barker et al 2018;Jacoby et al 2021;Chornay et al 2021;Chornay & Walton 2022). Mass-accreting WD binaries have been already observed as the central stars in some known PNe (Bode et al 1987;Guerrero et al 2004;Wesson et al 2008;Munari et al 2013;Maitra & Haberl 2022). Some WDs might accrete mass from their non-degenerate companions (Hamann et al 2003;Guerrero et al 2019;Jones et al 2019), a process that might explain some puzzles, like the luminosity function of PNe (Ciardullo 2016;Davis et al 2018;Souropanis et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Central stars of ∼20% of known PNe are reported to be close binaries (e.g., Bond 2000;Miszalski et al 2009), and it is increasing with deeper sky surveys like Kepler and Gaia (e.g., Barker et al 2018;Jacoby et al 2021;Chornay et al 2021;Chornay & Walton 2022). Mass-accreting WD binaries have been already observed as the central stars in some known PNe (Bode et al 1987;Guerrero et al 2004;Wesson et al 2008;Munari et al 2013;Maitra & Haberl 2022). Some WDs might accrete mass from their non-degenerate companions (Hamann et al 2003;Guerrero et al 2019;Jones et al 2019), a process that might explain some puzzles, like the luminosity function of PNe (Ciardullo 2016;Davis et al 2018;Souropanis et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This question is not rhetorical, as several direct and indirect observational evidence indicate that mass accretion takes place in several binary central stars of PNe. For instance, binary systems related to accreting WDs such as classical novae (Bode et al 1987;Wesson et al 2008), symbiotic stars (Guerrero et al 2004;Santander-García et al 2004;Corradi et al 2011;Munari et al 2013;Iłkiewicz et al 2018;Akras et al 2019) and supersoft X-ray sources (Kahabka et al 2008;Hutchings et al 2001;Mereghetti et al 2010;Maitra & Haberl 2022) have been observed to be hosted in the centres of PNe. Mass accretion processes have also been suggested to take place at the central stars of the PNe N66 (Hamann et al 2003) and the Eskimo Nebula (Guerrero et al 2019) as a plausible explanation for the two optical outbursts and the variable X-ray emission observed at the centre of the two nebulae, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…),Parker et al (2012b),Miszalski et al (2013),Aller et al (2013), Blanco Cárdenas et al (2013,Frew et al (2013),Munari et al (2013, see Frew et al 2014c),Yuan & Liu (2013),Miranda et al (2014),Miszalski & Miko lajewska (2014),Chhetri et al (2015) andKanarek et al (2016).…”
mentioning
confidence: 97%